2010
DOI: 10.1007/s12011-010-8725-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subchronic Aluminum Exposure on Serum Concentrations of Iron and Iron-Associated Proteins in Rats

Abstract: The purpose of the study was to investigate the effect of subchronic aluminum (Al) exposure on iron (Fe) homeostasis in rats. One hundred Wistar rats were divided into two groups. Experimental rats were given drinking water containing aluminum chloride (AlCl(3), 430 mg Al(3+)·L(-1)), while control rats were given distilled water for up to 150 days. Ten rats were sacrificed in each group every 30 days. Mean corpuscular hemoglobin (MCH), and serum levels of Al, Fe, transferrin (TF), total iron binding capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…The accumulation of Al can cause toxicity on the brain, kidney, bone, and hematopoietic systems, which is linked to the development of Alzheimer's disease, Parkinson's disease, dialysis dementia, osteomalacia, and microcytic hypochromic anemia. In addition, the accumulation of Al in the blood damages the structure and function of erythrocyte, and ultimately induces blood disorders [5,6]. Studies suggested that toxic metals can induce hypertension in humans and animals [7][8][9][10][11], and high Al content in plasma was related to hypertension [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of Al can cause toxicity on the brain, kidney, bone, and hematopoietic systems, which is linked to the development of Alzheimer's disease, Parkinson's disease, dialysis dementia, osteomalacia, and microcytic hypochromic anemia. In addition, the accumulation of Al in the blood damages the structure and function of erythrocyte, and ultimately induces blood disorders [5,6]. Studies suggested that toxic metals can induce hypertension in humans and animals [7][8][9][10][11], and high Al content in plasma was related to hypertension [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that Al is a systemic toxicant [4], and our previous researches have demonstrated that Al has adverse effects on the brain [5], bone [6], immune function [7], and hematopoietic system [8]. For now, several studies showed the toxic effects of Al on the reproductive system of male animals [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased erythrocytes number following Al exposure was observed in rats in our previous research [10]. Decreased erythrocytes number should lead to decreased immune function of erythrocytes following Al exposure, as E-CR1 existed on the erythrocytes membrane.…”
Section: Discussionmentioning
confidence: 61%
“…You et al [6] showed that immune function of erythrocytes in older dementia senilis mice was inhibited by AlCl 3 of 100 mg/kg body weight in drinking water. In our previous research the number of erythrocytes in rats was also reduced by AlCl 3 at dose of 67-100 mg/kg body weight per day in drinking water [10]. This experiment was used to offer a service to those people at a risk of oral exposure of different doses of Al.…”
Section: Discussionmentioning
confidence: 98%